UNDERSTANDING LETTER OF CREDIT - Katarina Hapsari (Universitas Stikubank (UNISBANK) Semarang, 2008)
English language is commonly used worldwide, but English for Specific Purposes might be used and understood easily by those who are involved in the field of study or business. One of them is the English language used in Letter of Credit (LC) is common for those who are involved in export/import business. Nevertheless, common people who are not involved in or well-informed about this kind of business might find it difficult to understand the content of LC, which is mostly written in businesslike English language. This paper is trying to provide the bridge to link the gab between the content of LC and their interpretation in terms of daily English language.